2022
DOI: 10.1038/s41392-022-00984-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of NVSI-06-07 as a heterologous booster after priming with BBIBP-CorV: a phase 2 trial

Abstract: The increased coronavirus disease 2019 (COVID-19) breakthrough cases pose the need of booster vaccination. We conducted a randomised, double-blinded, controlled, phase 2 trial to assess the immunogenicity and safety of the heterologous prime-boost vaccination with an inactivated COVID-19 vaccine (BBIBP-CorV) followed by a recombinant protein-based vaccine (NVSI-06-07), using homologous boost with BBIBP-CorV as control. Three groups of healthy adults (600 individuals per group) who had completed two-dose BBIBP-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 45 publications
5
14
0
Order By: Relevance
“…Preclinical animal studies showed that NVSI-06-09 elicited higher cross-neutralization to Omicron and other circulating variants than NVSI-06-07. 12 Comparing the results of this trial with the data from the trial on NVSI-06-07 reported previously, 11 the nAb levels boosted by NVSI-06-09 were remarkably higher than those by NVSI-06-07 against SARS-CoV-2 variants, especially Omicron. It should be mentioned that most of the participants in this trial had received three doses of BBIBP-CorV before booster vaccination, and those in the trial for NVSI-06-07 received two doses.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Preclinical animal studies showed that NVSI-06-09 elicited higher cross-neutralization to Omicron and other circulating variants than NVSI-06-07. 12 Comparing the results of this trial with the data from the trial on NVSI-06-07 reported previously, 11 the nAb levels boosted by NVSI-06-09 were remarkably higher than those by NVSI-06-07 against SARS-CoV-2 variants, especially Omicron. It should be mentioned that most of the participants in this trial had received three doses of BBIBP-CorV before booster vaccination, and those in the trial for NVSI-06-07 received two doses.…”
Section: Discussionsupporting
confidence: 56%
“…As an advanced vaccine developed based on NVSI-06-07, our first-generation trimeric RBD-based vaccine targeting the prototype SARS-CoV-2 virus, 10,11 NVSI-06-09 exhibited stronger immunogenic activities against the immune-evasive variants, including Omicron. Preclinical animal studies showed that NVSI-06-09 elicited higher cross-neutralization to Omicron and other circulating variants than NVSI-06-07.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epitopes in less accessible regions of the RBD are more conserved among circulating coronaviruses, consistent with Abs targeting these regions being able to cross-neutralize other coronaviruses [21,25,26]. Several groups have developed adjuvanted RBD only vaccines based on monomeric or multivalent display of the RBD, with several human phase I/II and phase III trials showing a safe and immunogenic response, thus making the RBD, or S in the RBD-open state, an attractive vaccine antigen [27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 75%
“…The copyright holder for this preprint this version posted November 29, 2022. ; https://doi.org/10.1101/2022.11.29.518231 doi: bioRxiv preprint have developed adjuvanted RBD only vaccines based on monomeric or multivalent display of the RBD, with several human phase I/II and phase III trials showing a safe and immunogenic response, thus making the RBD, or S in the RBD-open state, an attractive vaccine antigen [27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%